Genetic polymorphisms in CYP3A5 and MDR1 genes and their correlations with plasma levels of tacrolimus and cyclosporine in renal transplant recipients - Mendes, J (2009)
Immunosuppressive drugs, such as tacrolimus (FK506) and cyclosporine (CsA), play an essential role in graft survival, preventing rejection. Large interindividual differences in drug-metabolizing enzymes as well as in drug transporters make the task of reaching the optimal concentrations difficult. The bioavailability of CsA and FK506 seems to be associated with the cytocrhome P450 IIIA (CYP3A) gene. It has also been described that the Multi Drug Resistance 1 (MDR1) gene that encodes for polyglycoprotein-P (P-gp) may influence the metabolizing action of FK506 and CsA. Therefore, we sought, to correlate single nucleotide polymorphisms (SNPs) in the CYP3A and MDR1 genes with the concentrations of FK506 and CsA. For this purpose we analyzed 2 groups of renal transplant recipients by sequencing: one receiving a CsA immunosuppressive regime, and other, an FK506-immunosuppression. This study showed that subjects in the FK506 group who had encoded the 1236C>T substitution in the MDR1 gene displayed 44.4% higher drug concentrations compared with ("wild-type") individuals. Individuals carrying the 2677G>T,A mutation showed FK506 concentrations that were 44.7% higher than the wild-type individuals. Concerning the CsA group, individuals carrying the 22915A>C substitution displayed CsA concentrations 52.1% higher than wild-type individuals